Language and society in Ottoman Algiers - Rezzag, Messaouda; Fedoul, Nacer (The International tax journal, 2025)
This study examines the relationship between language and society in Ottoman Algiers, highlighting how social structures shaped linguistic diversity and reflected cultural hierarchy. Using a historical-analytical approach based on primary sources, it shows that Arabic, Turkish, Amazigh, Hebrew, and hybrid languages like Lingua Franca and Ladino coexisted within a complex social fabric. Arabic dominated religion and education, Turkish governed administration, and Amazigh persisted locally. The research concludes that Ottoman Algiers was a vibrant space of cultural synthesis where multilingualism became a hallmark of Algerian identity.